2010
DOI: 10.1371/journal.pntd.0000856
|View full text |Cite
|
Sign up to set email alerts
|

C6/36 Aedes albopictus Cells Have a Dysfunctional Antiviral RNA Interference Response

Abstract: Mosquitoes rely on RNA interference (RNAi) as their primary defense against viral infections. To this end, the combination of RNAi and invertebrate cell culture systems has become an invaluable tool in studying virus-vector interactions. Nevertheless, a recent study failed to detect an active RNAi response to West Nile virus (WNV) infection in C6/36 (Aedes albopictus) cells, a mosquito cell line frequently used to study arthropod-borne viruses (arboviruses). Therefore, we sought to determine if WNV actively ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
268
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(294 citation statements)
references
References 49 publications
13
268
1
Order By: Relevance
“…21 Kenney and others 43 reported that Nahuirim virus, a newly characterized flavivirus from Brazil, reduces replication of WNV, Japanese encephalitis, and St. Louis encephalitis viruses in dually infected mosquito cell cultures. All of these in vitro experiments were conducted using C6/36 cells, which, unlike live mosquitoes, do not have a functional antiviral RNAi response, 44 thus the biological relevance of these in vitro results is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…21 Kenney and others 43 reported that Nahuirim virus, a newly characterized flavivirus from Brazil, reduces replication of WNV, Japanese encephalitis, and St. Louis encephalitis viruses in dually infected mosquito cell cultures. All of these in vitro experiments were conducted using C6/36 cells, which, unlike live mosquitoes, do not have a functional antiviral RNAi response, 44 thus the biological relevance of these in vitro results is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, work on the subject has centered exclusively on mosquito-arbovirus experimental systems. In Aedes mosquitoes and cell lines, an expanded family of Piwi proteins is expressed in somatic tissues, and viral-derived piRNAs (vpiRNAs) are produced from the genomes of several arboviruses (23,(25)(26)(27)(28)(29). Functional links among the piRNA pathway, arbovirus replication, and vpiRNA production have been described as well.…”
Section: Significancementioning
confidence: 99%
“…The results of the C6/36 multiplication kinetics experiments should be interpreted with caution, as this cell line was established from Aedes albopictus larva homogenates (40), which may not accurately represent the cell types and expression profiles of the mosquito midgut epithelium and other cell types associated with infection, dissemination, and transmission of JEV. The results of a recent study indicate that C6/36 cells lack a functional RNA interference (RNAi) response, suggesting that these cells may not accurately model mosquito-arbovirus interactions at the molecular level (41). However, others have demonstrated that reduced Sindbis virus (an alphavirus) replication efficiency in C6/36 cells correlated with poor experimental infection of Aedes aegypti and sharply reduced midgut infectivity and dissemination (42).…”
Section: Gi-b Emerged Inmentioning
confidence: 99%